Can habitat specialization patterns of Neotropical birds highlight vulnerable areas for conservation in the Atlantic rainforest, southern Brazil?. (August 2015) - dos Anjos, Luiz; Collins, Cathy D.; Holt, Robert D.; Volpato, Graziele H.; Lopes, Edson V.; Bochio, Gabriela M.
Highlights: This study characterizes the degree of forest-type specialization in suboscine birds in the Atlantic forest. We observed habitat specialization within and among forest-types. We also found communities can be characterized by bird species of similar degrees of specialization. The ability to identify habitat specialists may indicate high priority areas for conservation. Abstract: Patterns of habitat specialization can be used to infer conservation risks for species whose habitats are being degraded or lost due to anthropogenic activity. We assigned levels of forest type specialization to birds based on their occurrence and local abundance in three basic types of Atlantic rainforest in southern Brazil: seasonal semi-deciduous forest, mixed rainforest, and dense rainforest. We hypothesized that forest types would contain birds characterized by different levels of specialization. Specifically, we predicted that the dense forest would contain more specialists due to its higher plant species richness. Our study focused on a major clade of the suboscine Passeriformes (Thamnophilidae–Furnariidae), the majority of which are understory insectivorous species. We used field data from 16 locations including 35 sites spanning the major forest types in southern Brazil. We found (1) substantial variation in abundance among sampling locations for a single bird species within and between forest types; (2) species-specific associations with forest types; and (3) spatial aggregation among species that share similar levels of specialization. Using our method of qualitative scoring of forest type specialization, three species were considered habitat specialists ( Xenops minutus, Leptasthenura setaria, and Cranioleuca pallida ), twelve species were moderate specialists, sixteen were generalists, five were complete generalists, and twelve species were too rare to be included in the analysis. Contrary to our hypothesis, both mixed and dense forests were equally dominated by specialists. We discuss the implications of our approaches for conservation assessment and planning, both at the single-species level and for aggregate species in assemblages.